1994
DOI: 10.1149/1.2055012
|View full text |Cite
|
Sign up to set email alerts
|

Electrotransportation of Aniline Through a Perfluorosulfonate Ion‐Exchange Membrane

Abstract: Transport phenomena of aniline through Na +-, K § and Cs § of a perfluorosulfonate ion-exchange membrane, Nation | 117, under a flow of de current, electrotransportation, were investigated. In each form, an increase in transport number of aniliniumeation was observed in the current density range from 0.3 to 1.3 mA em -2. The transport number of the anilinium cation in Cs § was larger than that expected from the concentration and diffusion coefficient of the anitinium cation in Cs~-form Nafion. These aniline tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Neutral aniline absorbs light at a wavelength of 280 nm. 40 The absorbance changes at 230 and 280 nm indicated that anilinium is the predominant species in the solution. Moreover, the pH values were measured in the source and receiver solutions to ensure that the proportion of neutral aniline and anilinium cation was kept constant during the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral aniline absorbs light at a wavelength of 280 nm. 40 The absorbance changes at 230 and 280 nm indicated that anilinium is the predominant species in the solution. Moreover, the pH values were measured in the source and receiver solutions to ensure that the proportion of neutral aniline and anilinium cation was kept constant during the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance at a wavelength of 230 nm was used for measuring the anilinium concentration in the receiver solution. Neutral aniline absorbs light at a wavelength of 280 nm . The absorbance changes at 230 and 280 nm indicated that anilinium is the predominant species in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Figure 1, Huang reported that aniline can be adsorbed on the surface of Pt in the presence of hydrogen gas at 350K with parallel positioned aromatic benzene ring. Only a few studies on the diffusion of aniline through the perfluorosulfuric acid (PFSA) ion exchange membrane have been reported, although they have been studied with a sodium form of the membrane and not the proton form of the membrane 4,5 . Studies in which PANI film was synthesized by electrochemical potential cycling between 0.6 and 0.8 V (vs. DHE) was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of anilinic compounds from solution onto both carbon and Pt has been reported 1,2,3 . Only few studies on the diffusion of aniline through the perfluorosulfonated ion exchange membrane have been reported though they are the study with a metal form and not proton form exchanger 4,5 . The behavior of aniline might be more complicated than ammonia as a contaminant on PEMFC since it has not only catalytic activity but also hydrophobic properties related to an aromatic benzene ring even though they are both cationic species.…”
mentioning
confidence: 99%